DACA, Mobility Investments, and Economic Outcomes of Immigrants and Natives - Jimena Villanueva Kiser; Riley Wilson (CESifo GmbH, 2024)
Exploiting variation created by Deferred Action for Childhood Arrivals (DACA), we document the effects of immigrant legalization on mobility investments and economic outcomes. DACA increased both geographic and job mobility of young immigrants, leading them to high paying labor markets and licensed occupations. Employing these shifts, we examine whether these gains to immigrants are offset by losses among U.S.-born workers. Employment of U.S.-born workers grows in the occupations that DACA recipients shifted into after DACA is implemented, even when controlling for local demand. Spillover estimates are consistent with worker complementarities and suggest that immigrant legalization generates broader economic benefits.
Keywords: J15; K37; R23; 330; legal status; DACA; immigration; geographic mobility; job mobility; occupational licensing; local labor markets